Measuring peat motion and water table dynamics on tropical peatlands using high-resolution time-lapse camera in four different land cover types across South Sumatra and Central Kalimantan. Issue 1 (1st May 2022) - Sulaeman, Dede; Hafiyyan, Ihsan; Hamzah, Hidayah; Evans, Chris D; Jonay Jovani-Sancho, A; Jaya, Adi
Abstract: Peat soils are known to be the most capable soil type to store a huge amount of carbon. However, peatland ecosystems are often disturbed by anthropogenic activities such as excessive water drainage, leading to rapid peat subsidence and carbon loss. Due to its dynamic properties, peatland ecosystem needs to be monitored over time to prevent unwanted socio-economic and environmental impacts. Nonetheless, field measurement of peat motion and subsidence often requires complex and expensive tools. This research aims to measure peat motion and water table dynamics in four sites across South Sumatra and Central Kalimantan Provinces. Peat motion and water table data were observed using a time-lapse camera for approximately a year period. Results of this study showed a good relationship of peat surface motion and water table dynamics with R 2 values ranging from 0.74 and 0.95. In Central Kalimantan, peat surface motion indicates a downward motion with the amplitude of 1.66 cm and 0.56 cm, and net subsidence of 1.35 cm and 0.47 cm, over shrub and coconut plantation sites, respectively. In South Sumatra, peat surface showed a high degree of fluctuation, with amplitudes of 4.89 and 4.80 cm, and net subsidence of 1.70 and 0.62, observed on oil palm and forest sites, respectively.